2009
DOI: 10.4238/vol8-1gmr488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PML/RARα fusion gene transcripts that showed no t(15;17) with conventional karyotyping and fluorescent in situ hybridization

Abstract: ABStRACt. Acute promyelocytic leukemia (APL) is characterized by a reciprocal translocation, t(15;17)(q22;q11-21), resulting in the fusion of the promyelocytic leukemia (PML) and retinoic acid receptor alpha (RARα) genes. Using conventional cytogenetic methods, these translocations are normally detected in about 70-90% of patients; most negative results are due to technical problems or cryptic variants. These masked PML/RARα fusions can be identified by molecular analyses, such as reverse transcriptase-polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…17,18 Although critics might state a lack of clear-cut advantages in comparison with standard cytogenetic and molecular genetic diagnostics, GEP-based diagnostic platforms might be useful for the identification of patients with masked fusion proteins (like t(15;17) and t(8;21)) that are not detected by conventional cytogenetics or fluorescence in situ hybridization. 97,98 In addition, GEP-based diagnostic platforms can provide information comparable to that of multiple different cytogenetic and molecular genetic analysis within a single experiment. Thus, a fully integrated and robust microarray platform such as the AMLprofiler, which is currently evaluated within a prospective clinical trial, might deliver faster results and improve patient classification by allowing determination of the presence of t(8;21), t(15;17), inv (16), CEBPA double mutants, NPM1 mutations, as well as high expression levels of genes that recently have been shown to predict poor outcome (that is MECOM (EVI1), MN1, BAALC and ERG) within a single test (Skyline Diagnostics, Rotterdam, Netherlands http://www.amlprofiler.com/site/).…”
Section: Conclusion/perspectivesmentioning
confidence: 99%
“…17,18 Although critics might state a lack of clear-cut advantages in comparison with standard cytogenetic and molecular genetic diagnostics, GEP-based diagnostic platforms might be useful for the identification of patients with masked fusion proteins (like t(15;17) and t(8;21)) that are not detected by conventional cytogenetics or fluorescence in situ hybridization. 97,98 In addition, GEP-based diagnostic platforms can provide information comparable to that of multiple different cytogenetic and molecular genetic analysis within a single experiment. Thus, a fully integrated and robust microarray platform such as the AMLprofiler, which is currently evaluated within a prospective clinical trial, might deliver faster results and improve patient classification by allowing determination of the presence of t(8;21), t(15;17), inv (16), CEBPA double mutants, NPM1 mutations, as well as high expression levels of genes that recently have been shown to predict poor outcome (that is MECOM (EVI1), MN1, BAALC and ERG) within a single test (Skyline Diagnostics, Rotterdam, Netherlands http://www.amlprofiler.com/site/).…”
Section: Conclusion/perspectivesmentioning
confidence: 99%
“…FISH also failed to detect these cryptic insertions if locus-specific probes were not used. [3,20,21] however, these cryptic insertions could be easily detected by simple RT-PCR techniques. [3,20,21] According to most investigators, high-quality RNA and efficient RT were the crucial determinants for successful RT-PCR of PML-RARA [14,22,23] On account of frequent leukopenia and the associated coagulopathy, the yield and quality of RNA from diagnostic samples were frequently poor, and this led to failure and false negativity by RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The rearrangement in our case presumably involved a limited sequence of DNA that was insufficient to hybridize with the Vysis PML-RARA dual color probe, thus allowing the PML rearrangement to go undetected. Indeed, Choghule et al have previously reported a cryptic PML-RARA rearrangement in a patient who exhibited normal karyotype by both G-banding and FISH analysis (Choughule, et al 2009). Our case illustrates a limitation with the large genomic probes routinely used for FISH analysis, and highlights the need for molecular analysis of novel karyotypic abnormalities in leukemia.…”
Section: Discussionmentioning
confidence: 99%